Identification of a newly conserved SLA-II epitope in a structural protein of swine influenza virus - Baratelli, M.; Morgan, S.; Hemmink, Johanneke D.; Reid, E.; Carr, B.V.; Lefevre, E.; Montaner-Tarbes, S.; Charleston, B.; Fraile, L.; Tchilian, E.; Montoya, M. (Frontiers Media, 2020)
Despite the role of pigs as a source of new Influenza A Virus viruses (IAV) potentially capable of initiating human pandemics, immune responses to swine influenza virus (SwIV) in pigs are not fully understood. Several SwIV epitopes presented by swine MHC (SLA) class I have been identified using different approaches either in outbred pigs or in Babraham large white inbred pigs, which are 85% identical by genome wide SNP analysis. On the other hand, some class II SLA epitopes were recently described in outbred pigs. In this work, Babraham large white inbred pigs were selected to identify SLA II epitopes from SwIV H1N1. PBMCs were screened for recognition of overlapping peptides covering the NP and M1 proteins from heterologous IAV H1N1 in IFNγ ELISPOT. A novel SLA class II restricted epitope was identified in NP from swine H1N1. This conserved novel epitope could be the base for further vaccine approaches against H1N1 in pigs.